O Projeto Africanidade e o Contexto Educacional a Guiné Bissau. - Correia, Heldomiro Henrique (2013)
This paper aims to make a contribution to the study of Guinean educational system, with the purpose of presenting systematic data, that contributes to addressing the shortcomings of the literature on the educational situation of the country. The objective of this work is to study the evolution of the educational system of Guinea-Bissau, between the years 1974 and 2012, considering its historical conditions, socioeconomic, and educational policies and their effects on the development of the country. We also have analyzed the impact of the Project Africanidade in this context. For the construction of the analysis, we used the approach of ex post factoresearch, since the research has raised the relations of cause and effect between various facts and phenomena. Questionnaires on the importance of improving the educational system of Guinea were administered to students, teachers and mediators of this project.